Author Correction: Regional variation limits applications of healthy gut microbiome reference ranges and disease models. (December 2018) - He, Yan; Wu, Wei; Zheng, Hui-Min; Li, Pan; McDonald, Daniel; Sheng, Hua-Fang; Chen, Mu-Xuan; Chen, Zi-Hui; Ji, Gui-Yuan; Zheng, Zhong-Dai-Xi; Mujagond, Prabhakar; Chen, Xiao-Jiao; et al.
In the version of this article originally published, in the sentence "Applying the same approach to obesity (Fig. 2b), MetS (Fig. 2c) and fatty liver (Fig. 2d) yielded similar results, " two figure panels were cited incorrectly. The data for obesity are in Fig. 2c, and the data for MetS are in Fig. 2b. The sentence has been updated with the correct citations in the print, PDF and HTML versions of the article.